1982
DOI: 10.4296/cwrj0702181
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Proposed Cage Fish Culture on Loch Lomond, an Important Reservoir in Central Scotland

Abstract: PnoposaLs to farrn z.ainbou tz'out (Salmo gaiTdnez,i)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The influence of physical site-specific characteristics, such as water exchange and bottom dynamic conditions, on the eutrophication effect in the recipient has been discussed by Hskanson (1986). Studies have shown enrichments of organic matter and nutrients in surrounding waters and sediments, oxygen depletion within cages, and qualitative and quantitative changes of the pelagic and benthic biota around and below farms (Beveridge & Muir 1982, Korzeniewslu & Korzeniewska 1982, Penczak et al 1982, Enell & Lof 1983, Enell 1985, Ervik et al 1985, Phillips et al 198513, Rosenthal 1985, Trojanowski et al 1985, Persson 1986, Brown et al 1987, Aure et al 1988. Most of these studies were carried out in fresh or (in one case) brackish waters, and very few of them attempted to quantify the efflux of solutes from particles deposited on the bottom and the accumulation of material in the sediment.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of physical site-specific characteristics, such as water exchange and bottom dynamic conditions, on the eutrophication effect in the recipient has been discussed by Hskanson (1986). Studies have shown enrichments of organic matter and nutrients in surrounding waters and sediments, oxygen depletion within cages, and qualitative and quantitative changes of the pelagic and benthic biota around and below farms (Beveridge & Muir 1982, Korzeniewslu & Korzeniewska 1982, Penczak et al 1982, Enell & Lof 1983, Enell 1985, Ervik et al 1985, Phillips et al 198513, Rosenthal 1985, Trojanowski et al 1985, Persson 1986, Brown et al 1987, Aure et al 1988. Most of these studies were carried out in fresh or (in one case) brackish waters, and very few of them attempted to quantify the efflux of solutes from particles deposited on the bottom and the accumulation of material in the sediment.…”
Section: Introductionmentioning
confidence: 99%
“…L. Awe & L. Earn) where the environmental impact on the water body as a whole is likely to be slow to develop because of the large physical 'buffering' (Bailey-Watts & Duncan, 1981). Nevertheless, there is concern about eutrophication where cage farming in lochs used for supplying drinking water, such as Loch Lomond, has been proposed (Beveridge & Muir, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…• Todos los autores, coinciden en señalar que el principal problema en el cultivo de jaulas flotantes, es generado por el enriquecimiento en nutrientes y materia orgánica disuelto o en forma de partículas. La introducción en el ambiente de nutrientes y piensos, que acompaña siempre a las operaciones de explotación intensiva, es quizás elemento que más impacta el medio en que se desarrolla este tipo de producciones, muchos autores han mencionado las pérdidas de piensos desde los años 70 (Beveridge y Muir, 1982).…”
Section: Resultsunclassified